Construction Work Cost Determination - Koba, Ðžlena; Myronova, Yulia; Byba, Volodymyr (International Journal of Engineering and Technology, 2018)
The main Ukraine construction industry tendencies during 2010-2017 are described in the article. The order of construction and installation work formation is determined. The practical application peculiarities of cost calculations traditional and alternative methods in construction industry are considered. Based on the principles, methods and tools created a new conceptual model construction work cost determination.Â Â
Keywords: Ñalculation methods; Ñonstruction and installation work cost; construction industry; Ñosts; financial statements.